Chemotaxonomy of the Ericales. (August 2015) - Nascimento Rocha, Marco Eduardo do; Figueiredo, Maria Raquel; Coelho Kaplan, Maria Auxiliadora; Durst, Tony; Arnason, John Thor
Abstract: The order Ericales, sensu APG III, belongs to the Asterids. It comprises around 25 families and 347 genera distributed in 4 clades: Balsaminoids, Polemonioids, Primuloids and Ericoids. Their species are widely distributed in arctic, temperate and tropical regions. A comparison between phylogenetic and chemical data for Ericales demonstrated a low correlation, except for Primuloid families. Flavonoids and triterpenes were characterized as good taxonomic markers for the order, due to their general occurrence and molecular diversity. Nevertheless, saponins are markers only for Primulaceae and lignans are the exclusive markers for Styracaceae. Analyses of correlation among chemical parameters based on flavonoidal, morphological and chemo-morphological indexes, showed low phylogenetic affinity for certain groups, positioning Primuloids and Balsaminoids as the highest and the lowest evolutionary advanced taxa, respectively. Flavonoids produced are mainly flavonols rather than flavones. Hydroxyl protection occurs mainly by glycosylation and to a lesser extent by methylation. These data confirmed the primitive status for the order. Highlights: The chemosystematics new arrangement of Ericales, sensu APG III has been reported. The comparison among phylogenetic and phytochemical data showed low correlation. Flavonoids and triterpenes were the main taxonomic markers for Ericales. The flavonoid hydroxyl groups are protected mainly by mechanism of glicosilation. Analyses of evolutionary parameters confirmed the primitive status for the order Ericales.